The Influence of Company Age, Profitability, and Leverage on Tax Avoidance in Pharmaceutical Sector Companies Listed on The Indonesian Stock Exchange (BEI) - Amin Hou; Ahmad Fadli; Deborah tambunan; Muhammad Restu Razaq; Rina Asriani Levianti (International Journal of Economics, Business and Innovation Research, 2023)
This research was conducted to analyze factors that can influence tax avoidance in a company. The dependent variable used in this research is tax avoidance and the dependent variables are company age, profitability, and leverage. The population selected in this research is all companies in the pharmaceutical sector and listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The research method used was purposive sampling with several predetermined criteria. The type of data uses secondary data from companies that have provided financial information or gone public. Data analysis uses SPSS software by carrying out multiple regression analysis tests. The results of this research prove that the profitability and leverage variables influence corporate tax avoidance, while company age does not influence a company's tax avoidance.